A Urodynamic Comparison of Neural Targets for Transcutaneous Electrical Stimulation to Acutely Suppress Detrusor Contractions Following Spinal Cord Injury - Doherty, Sean; Vanhoestenberghe, Anne; Duffell, Lynsey; Hamid, Rizwan; Knight, Sarah (Frontiers in Neuroscience, 2019)
Objectives: To assess and compare the effect of transcutaneous Dorsal Genital Nerve Stimulation (DGNS), Tibial Nerve Stimulation (TNS), Sacral Nerve Stimulation (SNS) and Spinal Stimulation (SS) on Neurogenic Detrusor Overactivity (NDO) and bladder capacity in people with Spinal Cord Injuries (SCI). Materials and methods: Seven male participants with supra-sacral SCI were tested. Standard cystometry (CMG) was performed to assess bladder activity at baseline and with stimulation applied at each site. This was conducted over four separate sessions. All stimulation was monophasic, 15 Hz, 200 S pulses and applied at maximum tolerable amplitude. Results were analysed against individual control results from within the same session. Results: DGNS increased bladder capacity by 153±146 ml (p=0.016) or 117±201%. DGNS, TNS and SNS all increased the volume held following the first reflex contraction, by 161±175, 46±62 and 34±33 ml (p=0.016, p=0.031, p=0.016), respectively. SS results showed small reduction of 33±26 ml (p=0.063) from baseline bladder capacity in 5 participants. Maximum Detrusor Pressure before leakage was increased during TNS, by 10±13 cmH2O (p=0.031) but was unchanged during stimulation of other sites. DGNS only was able to suppress at least one detrusor contraction in 5 participants and reduced first peak detrusor pressure below 40 cmH2O in these 5. Continuous TNS, SNS and SS produced non-significant changes in bladder capacity from baseline, comparable to conditional stimulation. Increase in bladder capacity correlated with stimulation amplitude for DGNS but not TNS, SNS or SS. Conclusions: In this pilot study DGNS acutely suppressed detrusor contractions and increased bladder capacity whereas TNS, SNS and SS did not. This is the first within individual comparison of surface stimulation sites for management of NDO in SCI individuals.